The role of individual temperament, family and peers in social anxiety disorder: A controlled study - Marina Cunha; Isabel Soares; José Pinto-Gouveia (International Journal of Clinical and Health Psychology, 2008)
In the present ex post facto study the influence of inhibition, attachment styles, parental rearing styles and social comparison in social anxiety disorder was investigated. First, we studied the isolated effect of each variable through the comparison of two clinical groups and a control group. Then we analysed the action of these variables altogether, using the structural equation model, controlling eventual mediator effects. The sample consisted of adolescents with ages between 12 and 18 years old, who were distributed by three comparison groups: social phobia, other anxiety disorders and normal controls. A structured clinical interview and self-report instruments were used for/in youth assessment. Results showed a specific effect of inhibition and social comparison in social anxiety disorder. The structural equation model outlined the combined action of inhibition, social comparison and peers attachment quality in what concerns the prediction of social anxiety as well as the mediation role of social comparison through the effect of other variables. Although this study presents some limitations, its results contribute to the understanding of some of the ways of development and maintenance of social anxiety during adolescence.